Bad rules rather than slow discretion? A critical appraisal of EU stabilisation policy - Bernd Lucke; Bodo R. Neumann (International Journal of Economic Policy Studies, 2021)
The EU reacted swiftly to the economic dimension of Covid-19 by designing new instruments to support the fiscal policy of Member States. But entry into force and implementation was slow due to various political hurdles with little action taking effect by the end of 2020. In a draft law currently under consideration in the European Parliament, the Commission proposes speedier crisis responses using a rules-based approach. We analyse the legal and economic aspects of this so-called "European Investment Stabilisation Function" (EISF) and argue that a rules-based policy may be inefficient and detrimental to important EU policy objectives. For instance, in the Covid-19 crisis, most of the EISF funds would have supported only the wealthiest Member States. In general, we show that well-intended EU-funded stabilisation measures may actually be counterproductive in terms of EU cohesion, suboptimal in terms of stabilisation and regressive in terms of cross-country income distribution.
Keywords: E62; H77; 330; Fiscal union; Stabilisation function; Eurozone budget; Cohesion policy